International Politics of the Persian Gulf: By Mehran Kamrava (New York: Syracuse University Press, 2011. 374 pages.) (American Journal of Islam and Society, 2013)
The Persian Gulf region is home to the six members of the Gulf CooperationCouncil (viz., Oman, the UAE, Qatar, Bahrain, Kuwait, and Saudi Arabia),Iran, and Iraq. Holding over 60 percent of the world’s oil and over 40 percentof its natural gas reserves, the Persian Gulf is central to the global economy.Yet a dominant regional power is lacking; beginning with the British in thelate nineteenth century, foreign powers have consistently been meddling inthe region. Significant economic, social, cultural, and political changes havetransformed the region’s international relations since Britain’s withdrawal inthe 1960s. The contributors to this volume, which provides a rich account ofthis transformation, focus on natural resources, the Iranian-Saudi competition,the interest of major external actors, and political reform.The volume’s main thrust is the centrality of both state and regime securityin order to understand the region. The volume’s editor, Mehran Kamrava,notes that the international politics there is essentially that of securitypolitics. He offers four reasons for this: (1) its central role in oil and naturalgas production and, increasingly, global finance, (2) the competition betweenIran and Saudi Arabia over regional leadership, (3) the long-standingAmerican-Iranian conflict, and (4) the instability brought about by intermixingpolitics and religion.He identifies three poles of power that shape the region’s security dynamics:the American pole; the GCC pole, which is centered on Saudi militaryand Qatari-UAE financial power; and the Iranian pole, which relies both onmilitary might and soft power. Since the Iranian revolution, the American andthe GCC poles have built a resilient alliance that has been driven by both theUnited States’ growing direct involvement and the GCC’s failure to providesecurity to its members.The chapters, written by leading regional specialists, further elaborate onthe region’s security dynamics. In Chapter 2, J. E. Petersen offers a useful typologyof boundary formation. He discusses how the state-building process,historical claims, colonial imposition, and resource competition have shapedstate boundaries. As these boundaries remain contested, Petersen details variousongoing problems. In Chapter 3, Fred H. Lawson refines the concepts “securitydilemma” and “alliances dilemma” and uses them to explain the arms race inthe Gulf since the first Gulf War. Middle East specialists and international relationsscholars will find these chapters useful in conceptual refinement ...